Hamdan Zoelva's Political Thoughts in the Book Constitutional Struggle - Andjani, Alifia; Munandar, Moh. Aris; Beny Mukti Setiyawan, Wahyu; Hardi Saputro, Iwan (Unnes Political Science Journal, 2024)
Political thought has a crucial role in determining policies and shaping the ideal social order. In Indonesia, various ideologies are present, including Pancasila as the foundation of the state as well as the concepts of pluralism, nationalism, and democracy. Hamdan Zoelva's thought emphasizes the importance of the constitution as the basic norm of the state of law and the protector of human rights. Hamdan criticized liberalism and capitalism which he considered could erode the values of Pancasila in Indonesia's political and economic system. In his book Constitutional Struggle, he warns that the dominance of capitalism must be controlled according to the principles of Pancasila. This research aims to 1) understand Hamdan Zoelva's political journey, and 2) find out the causes of his political thinking about the constitution. The research data includes primary and secondary sources, processed through interviews and documentation. The validity of the data was checked by examining Hamdan's background, such as his curriculum vitae, education, influence, and political and cultural conditions at the time. The results of the study show that Hamdan Zoelva sees the constitution as the will of the people that must be respected. He emphasized the role of the Constitutional Court (MK) in maintaining the balance of power and protecting human rights. However, Hamdan criticized the amendment to the 2024 Constitutional Court Law which he considered threatening the independence of judges.